APPLE’S CONSTRUCTION OF ITS BRAND AS CULTURAL CAPITAL IN APPS WE CAN’T LIVE WITHOUT COMMERCIAL - Clifford L.D. Sangari; Priska Febrinia Handojo (Institute of Research and Community Outreach - Petra Christian University, 2015)
Commercial is an advertising strategy to promote a product or service effectively through mass media. It is also attractive because it touches the audience’s emotion through its music, cinematography, and storytelling. However, commercial has hidden meaning and this meaning represents the brand as symbols which distinct itself and its users to other brands’. I analyze Apps We Can’t Live Without (2014) commercial as the text to show Apple encodes meaning and transmit it to the society. Using film language and Bourdieu’s cultural capital theory, the findings show that the symbols from the commercial bring into a conclusion that Apple as a brand is a symbolic capital, specifically cultural capital. The people who has the brand is considered to have higher position in its fields which are Apple and gadget communities.